GPX4 Plays a Crucial Role in Fuzheng Kang’ai Decoction-Induced Non-Small Cell Lung Cancer Cell Ferroptosis - Zhao, Yue-Yang; Yang, Yu-Qi; Sheng, Hong-Hao; Tang, Qing; Han, Ling; Wang, Su-Mei; Wu, Wan-Yin (Frontiers in Pharmacology, 2022)
Background: Fuzheng Kang’ai decoction (FZKA) has been widely used to treat Non-Small Cell Lung Cancer (NSCLC) patients in China for decades, showing definitively curative effects in clinic. Recently, we found that FZKA could induce NSCLC cell ferroptosis, another type of programmed cell death (PCD), which is totally different from cell apoptosis. Therefore, in the present study, we aim to discover the exact mechanism by which FZKA induces NSCLC cell ferroptosis, which is rarely studied in Traditional Chinese Medicine (TCM). Methods: Cell proliferation assay were performed to detect the cell viability. Cell ferroptosis triggered by FZKA was observed by performing lipid peroxidation assay, Fe2+ Ions assay, and mitochondrial ultrastructure by transmission electron microscopy. Ferroptosis inhibitors including liproxstatin-1 and UAMC 3203 were used to block ferroptosis. The ratio of GSH/GSSG was done to measure the alteration of oxidative stress. Western blot and qRT-PCR were carried out to detect the expression of SLC7A11, SLC3A2, and glutathione peroxidase 4 (GPX4) at protein and mRNA levels, respectively. Lentivirus transfection was performed to overexpress GPX4 stably. Animal model was done to verify the effect of FZKA-induced ferroptosis in NSCLC in vivo and immunohistochemistry was done to detect the expression of SLC7A11, SLC3A2 and GPX4 at protein level. Results: First of all, in vitro experiments confirmed the inhibition effect of FZKA on NSCLC cell growth. We then, for the first time, found that FZKA induced NSCLC cell ferroptosis by increasing lipid peroxidation and cellular Fe2+ Ions. Moreover, characteristic morphological changes of NSCLC cell ferroptosis was observed under transmission electron microscopy. Mechanistically, GPX4, as a key inhibitor of lipid peroxidation, was greatly suppressed by FZKA treatment both at protein and mRNA levels. Furthermore, system xc- (SLC7A11 and SLC3A2) were found to be suppressed and a decreased GSH/GSSG ratio was observed at the same time when treated with FZKA. Notably, overexpressing GPX4 reversed the effect of FZKA-induced NSCLC cell ferroptosis significantly. Finally, the above effect was validated using animal model in vivo. Conclusion: Our findings conclude that GPX4 plays a crucial role in FZKA-induced NSCLC cell ferroptosis, providing a novel molecular mechanism by which FZKA treats NSCLC.